2018
DOI: 10.1177/0163443718813470
|View full text |Cite
|
Sign up to set email alerts
|

Advancing children’s news media literacy: learning from the practices and experiences of young Australians

Abstract: Social media use has redefined the production, experience and consumption of news media. These changes have made verifying and trusting news content more complicated and this has led to a number of recent flashpoints for claims and counter-claims of ‘fake news’ at critical moments during elections, natural disasters and acts of terrorism. Concerns regarding the actual and potential social impact of fake news led us to carry out the first nationally representative survey of young Australians’ news practices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Thus, when faced with clickbait-type content on YouTube, about a child who apparently receives a beating, they display a certain reluctance to share it. Although, on the contrary, probably resulting from their ignorance or naivety, teens share with the intention of “informing others” contents of their interest, which affects them or which is very spectacular (Figueira & Oliveira, 2017; Loos et al, 2018; Notley et al, 2017; Sbardella, 2017; Tickle, 2018; Wineburg et al, 2016). It is also possible that, within this eagerness to inform others underlies, as Marwick (2018) and Fernández and Fernández (2017) pointed out, the need to reaffirm one’s identity or to convey certain affinities, ideologies, or interests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when faced with clickbait-type content on YouTube, about a child who apparently receives a beating, they display a certain reluctance to share it. Although, on the contrary, probably resulting from their ignorance or naivety, teens share with the intention of “informing others” contents of their interest, which affects them or which is very spectacular (Figueira & Oliveira, 2017; Loos et al, 2018; Notley et al, 2017; Sbardella, 2017; Tickle, 2018; Wineburg et al, 2016). It is also possible that, within this eagerness to inform others underlies, as Marwick (2018) and Fernández and Fernández (2017) pointed out, the need to reaffirm one’s identity or to convey certain affinities, ideologies, or interests.…”
Section: Resultsmentioning
confidence: 99%
“…Their access takes place mainly through social media, where secondary sources and contents received from their friends are more highly valued than the original source of information. They display little interest in the accuracy of a news item in favor of contents that really affect them, preferably of a humorous, striking, or novel nature (Austrian Safer Internet Center, 2017; Figueira & Oliveira, 2017; Greek Safer Internet Center, 2019; Loos et al, 2018; Notley et al, 2017; Sbardella, 2017; Tickle, 2018; Wineburg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While studies have argued that media educators can play a role in fostering such forms of civic engagement (e.g. Notley and Dezuanni, 2019), the interviews particularly highlight the importance of parents in this process. In families where parents regularly consumed news, current affairs were a frequent topic of discussion, both face-to-face and online, such as for Sanne (18 years) who mainly followed the news through links shared in her family's WhatsApp group.…”
Section: Engaging With Newsmentioning
confidence: 98%
“…A 2018 study found that media literacy in the Australian Curriculum was 'developed in the pre-digital era [with] the resources available in many schools … informed by understandings about legacy media and communications' and that 'there have thus far been very few efforts to reconceptualise media literacy for digital contexts within educational policy.' 1310 Similarly, a review of digital media literacy in Tasmanian schools concluded that 'more clarity is required for teachers from school and curriculum authorities regarding media literacy instruction and the priority it should be given in Australian classrooms'. 1311 Several stakeholders support increasing digital media literacy education beyond the approach of the current Australian Curriculum.…”
Section: Digital Media Literacy As a Tool To Combat Information Disordermentioning
confidence: 99%